Designing and Supporting Virtual Exchange: The Case of Chinese–English e-Tandem. Issue 1 (17th December 2021) - Lewis, Tim; Qian, Kan
This article examines how adult distance learners with limited levels of second language (L2) proficiency can engage in and benefit from e-tandem learning and to what extent intercultural learning takes place in the context of a six-week guided e-tandem project. While UK participants have completed a one-year beginners' Chinese course at the Open University, their proficiency level in Chinese remains modest (between A1 and A2 on the Common European Framework of Reference scale). Their Chinese counterparts are undergraduates at Beijing Foreign Studies University with eight years of studying English behind them and majoring in English. This asymmetry presents particular challenges. Through analysis of email exchanges, transcripts of Skype conversations and interviews, surveys, and learning diaries, we research learner engagement and development as well as identifying areas where the design of the exchange might be improved and support for less advanced learners strengthened. Our findings suggest that while there is significant evidence of L2 development and intercultural learning, this can come at a high price for learners. Our conclusion, based on participant feedback, outlines modifications to the standard e-tandem model which might provide more effective support for those who are struggling and make for a less challenging but equally enriching experience. These findings have pedagogical implications for the future design of e-tandem projects, in particular how to best support e-tandem exchanges involving asymmetry, or where participants have limited L2 proficiency.